2020
DOI: 10.1038/s41598-020-73376-7
|View full text |Cite
|
Sign up to set email alerts
|

RNA oxidation in chromatin modification and DNA-damage response following exposure to formaldehyde

Abstract: Formaldehyde is an environmental and occupational chemical carcinogen implicated in the damage of proteins and nucleic acids. However, whether formaldehyde provokes modifications of RNAs such as 8-oxo-7,8-dihydroguanine (8-oxoG) and the role that these modifications play on conferring long-term adverse health effects remains unexplored. Here, we profile 8-oxoG modifications using RNA-immunoprecipitation and RNA sequencing (8-oxoG RIP-seq) to identify 343 RNA transcripts heavily enriched in oxidations in human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 110 publications
2
24
0
Order By: Relevance
“…While the mitochondrial mRNAs which are encoded in the mitochondrial genome had comparable oxidation levels to those of cytoplasmic mRNA under normal conditions, the mitochondrial mRNAs were oxidized distinctly higher than cytoplasmic mRNAs after H 2 O 2 treatment. Consistent with the findings of selective mRNA oxidation monitored with 8-oxo-G ( Shan and Lin, 2006 ; Görg et al, 2008 ; Bazin et al, 2011 ; Gonzalez-Rivera et al, 2020 ), the oxidation levels of mRNA based on the AP site quantity vary depending on mRNA studied. For instance, AP site levels of Oma1 mRNA were found to be about five-fold higher than that of ribosomal protein Rpl5 mRNA (unpublished data).…”
Section: Rna Oxidative Modificationssupporting
confidence: 79%
See 1 more Smart Citation
“…While the mitochondrial mRNAs which are encoded in the mitochondrial genome had comparable oxidation levels to those of cytoplasmic mRNA under normal conditions, the mitochondrial mRNAs were oxidized distinctly higher than cytoplasmic mRNAs after H 2 O 2 treatment. Consistent with the findings of selective mRNA oxidation monitored with 8-oxo-G ( Shan and Lin, 2006 ; Görg et al, 2008 ; Bazin et al, 2011 ; Gonzalez-Rivera et al, 2020 ), the oxidation levels of mRNA based on the AP site quantity vary depending on mRNA studied. For instance, AP site levels of Oma1 mRNA were found to be about five-fold higher than that of ribosomal protein Rpl5 mRNA (unpublished data).…”
Section: Rna Oxidative Modificationssupporting
confidence: 79%
“…Subsequent studies consistently showed selective mRNA oxidation in ALS patients’ brains, although which mRNAs were highly oxidized seemed to be different between ALS and AD ( Shan et al, 2003 ; Chang et al, 2008 ). Selective oxidation of mRNA was also reported in ripened seed ( Bazin et al, 2011 ), and other pathologies including ammonia toxicity ( Görg et al, 2008 ) and formaldehyde exposure ( Gonzalez-Rivera et al, 2020 ). Of note, highly oxidized mRNA species in their studies seemed to be inconsistent, suggesting that further study is necessary to clarify determinants to regulate selective mRNA oxidation.…”
Section: Rna Oxidative Modificationsmentioning
confidence: 90%
“…Recent studies have shown that CAP-generated reactive oxygen and nitrogen species (RONS) could induce 8-oxoguanine (8-oxoG) formation in nucleic acids [42]. To investigate the in situ 8-oxoG modification of RNA after CHCP treatment, we modified and generated a previously designed [43] human ribosomal protein S3 (hRpS3) peptide probe (TaT-S3-peptide) that binds tightly to 8-oxoG sites on RNA. Fluorescence signals were compared between CHCP-treated and untreated cells (Figure 6A), probed or not probed with TaT-S3-peptide (ANOVA for CAP-TaT-S3, mock-TaT-S3, CAP, and mock groups: F[3,44] = 587.78, p < 4.3 × 10 −33 ).…”
Section: Oxidation Of Rna After Chcp Treatmentmentioning
confidence: 99%
“…Ribosomal RNA (rRNA) was depleted using a Ribo-Zero Gold rRNA Removal Kit (Illumina, San Diego, CA, USA) following the manufacturer's instructions. Immunoprecipitations of 8-oxoGcontaining RNA transcripts were performed as described previously [43] in biological triplicates for CAP-treated 0 (CP0) and 1 h (CP1), mock zero-(MZ) and one-hour (M1) conditions. Briefly, each sample was divided into portions and a portion of the input RNA was incubated with 10 µg of 8-oxo-7,8-dihydroguanosine (8-oxoG) monoclonal antibody (Trevigen, Gaithersburg, MD, USA) in immunoprecipitation (IP) buffer (10 mM Tris pH 7.4, 150 mM NaCl, 0.1% IGEPAL, and 200 units/mL SUPERaseIn RNA inhibitor (ThermoFisher Scientific)) in a 1 mL reaction volume for 4 h at 4 • C with rotation.…”
Section: Pull-downmentioning
confidence: 99%
“…In vitro studies with primary cultures, further demonstrated that the presence of oxidised nucleobases in mRNA cause ribosome stalling on the transcripts, resulting in a decrease in protein expression, and neuronal deterioration, providing a mechanistic link [ 100 ]. These earlier findings are confirmed by recent data using an exciting new methodology, 8-oxoGua-RNA-immunoprecipitation and RNA sequencing which, given the functional relevance of the oxidised transcripts, led the authors to propose that RNA oxidation is an additional driver of cell physiology, health, and disease [ 101 ].…”
Section: Formation Repair and Consequences Of Damage To Nucleic Acidsmentioning
confidence: 68%